An Ethnomedicinal Study of Medicinal Plants from the Zingiberaceae Family Used by the Community in Nunggalrejo Village, Punggur Subdistrict, Central Lampung Regency - Malahatu Zalfa, Aisyah; Dwiningrum, Riza; Kartika Putri, Diah; Safutri, Wina (LPPM Universitas Dhyana Pura, 2025)
Ethnomedicine is a traditional treatment method that emphasizes local cultural practices and does not involve modern medical treatment. The community in Nunggalrejo frequently uses medicinal plants from the Zingiberaceae family to treat various ailments. Additionally, plants from this family are used in traditional medicine. The aim of this study is to analyze the species, plant parts used, preparation methods, and medicinal benefits of Zingiberaceae plants utilized in traditional medicine. This research employs a qualitative descriptive method with a snowball sampling technique and structured interviews. The research targets include herbal medicine makers, the oldest community members, and people who use traditional medicine. Based on interviews with 12 informants, the data revealed nine dominant species of Zingiberaceae, with the most frequently used being Curcuma xanthorrhiza (temulawak), Zingiber officinale (ginger), Curcuma longa (turmeric), and Kaempferia galanga (kencur), each accounting for 19%. The part most commonly used is the rhizome (100%), with boiling being the most common preparation method (50%). The most frequently treated ailment is acid reflux (29%). In conclusion, there are nine species of Zingiberaceae used to treat ten types of illnesses in Nunggalrejo Village.